(untitled) (University Heart Journal, 2014)
Coronary reperfusion with primary percutaneous coronary intervention (PPCI) or fibrinolytic therapy improves outcomes in patients with acute ST elevation myocardial infarction (STEMI) or an MI with a new or presumably new left bundle branch block or a true posterior MI. If performed in a timely fashion, PPCI is the reperfusion therapy of choice compared to fibrinolysis because it achieves a higher rate of TIMI 3 flow. Here we describe a case of acute ST elevated inferior myocardial infarction managed with primary percutaneous coronary intervention as a launching case in the University Cardiac Center ofBangabandhu Sheikh Mujib Medical University. DOI: http://dx.doi.org/10.3329/uhj.v9i1.19518 University Heart Journal Vol. 9, No. 1, January 2013; 67-69